Analysis of metrosexual consumer lifestyle in urban areas: A phenomenological study of male-targeted beauty consumers on social media - Arigi, Julio Pasha; Hidayat, Z.; Putra, Devi Olivia; Gulo, Agus (Humanities, Arts and Social Sciences Studies, 2024)
This in-depth study explores the evolving metrosexual consumer lifestyle within Indonesia’s urban centers and specifically delves into how the metrosexual community utilizes Instagram as a platform for self-representation and social interaction. Employing a qualitative, phenomenological approach anchored in constructivism, data were gathered through a multifaceted approach, including in-depth interviews with key informants, participant observation through examination of Instagram profiles and online interactions, as well as a comprehensive literature review to contextualize findings. To identify study participants, strategic keywords such as "metrosexual," "lifestyle," and "men’s beauty" were applied on Instagram search. The selection was meticulously narrowed down to ten highly active endorsers and followers with the most significant engagement. The approach ensured that rich insights from individuals deeply embedded within the metrosexual community on Instagram were captured. The study unveils intriguing aspects of Indonesian urban metrosexuals’ consumption habits and social media preferences. Their primary concern lies in the effectiveness of beauty products in enhancing their appearance, prioritizing results over mere brand prestige. The focus on practicality is further reflected in their preferred places to meet. Shopping malls emerge as their preferred destinations for social activities. When it comes to social media, Instagram is the most popular choice. Its visual focus and content sharing align perfectly with the metrosexual community’s interest in self-presentation and cultivating a meticulously crafted online image. The research also highlights the significant role of physical appearance in boosting self-esteem within the metrosexual community, influencing their interactions both online and offline. The managerial implications of this study indicate the importance of paying attention to male consumers for beauty products and services.